Bio-cement and bio-cementation - Liao, Jian Ting. (2010)
Construction on marine clay is challenging, as clay tendes to undergo liquefaction under a range of stress, resulting in landslides in extreme cases. Singapore has extensive land reclamation along its coastal areas. Currently this is done using cement columns mixed in situ at relevant sites. This is a cause of environmental concern due to the large amount of CO2 generated by the production of cement. Secondly Singapore faces a serious problem of sand shortage. This project aims to address both issues by adopting novel environmentally friendly approaches to strengthen the marine clay. The project explores the viability of several chemical based methods of strengthening using these components: addition of aluminum oxide (Al2O3), precipitation of calcium carbonate (CaCO3), precipitation of ferrous hydroxide (FeOH3) and precipitation of ferrous sulfide linkages (FeS). The project also explores microbial possibilities of replacing the chemicals, using urease producing bacteria (UPB) and sulfate reducing bacteria (SRB). Using these processes in the laboratory, strength up to 462 kPa (UCS) was achieved. A matrix of precipitation of ferrous hydroxide (FeOH3) with ferrous sulfide linkages (FeS) showed the most potential for further studies. Generally, compressive strength in all experiments increases up to 5 folds, with maximum increment in strength of up to 8 folds. Based on the preliminary results, the methods explored in this project are determined to be promising for cost-effective and efficient soft marine clay improvement with a wide range of potential applications. This technology utilizes waste products from the steel refining industry and water treatment industry as reagents to strengthen the clay. This report is relevant to all those involved in the use of industrial byproducts to improve soil and geotechnical properties. This report is part 1 of the final year report, EN63AB, Bio-cementation. For the missing contents, please refer to part 2 of the same project title submitted by Shah Rizan Shahdan.